(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2026)
Viscosity is a key physical property of biological fluids that determines their resistance to flow and directly influences circulation, tissue perfusion, and cellular transport. This article provides an in-depth analysis of the viscosity of biological fluids—primarily blood—integrating principles of fluid mechanics with physiological and clinical perspectives. The determinants of viscosity, including hematocrit, plasma protein concentration, temperature, and shear rate, are discussed alongside their role in normal physiology and disease states. Alterations in viscosity are shown to play a critical role in cardiovascular disorders, diabetes mellitus, and inflammatory conditions, making it an important diagnostic and prognostic parameter in modern medicine